684 LONG-TERM CONDITIONS, MULTIMORBIDITY, LIFESTYLE FACTORS AND GRIP STRENGTH CHANGE OVER 9 YEARS IN 44, 315 UK BIOBANK PARTICIPANTS. (8th March 2022) - Hurst, C; Murray, J C; Granic, A; Hillman, S J; Cooper, R; Sayer, A A; Robinson, S M; Dodds, R M
Abstract: Introduction: Weak grip strength is associated with a range of adverse health outcomes, and an accelerated decline in grip strength confers an even greater risk. To date there has been limited research into the factors associated with change in grip strength in mid-life. Using data from UK Biobank our aim was to investigate the associations of long-term conditions (LTCs), multimorbidity and lifestyle factors with patterns of change in grip strength. Methods: We used data from 44, 315 UK Biobank participants with grip strength measured at baseline (2006–10) and a subsequent study visit around nine years later. At baseline, participants' LTCs were self-reported and categorised against a hierarchy. Multimorbidity was characterised by the number of LTC categories present (0, 1, 2 and 3+). Lifestyle factors (body mass index (BMI), smoking, diet and physical activity) were also assessed. Change in grip strength was grouped into four patterns: decline, stable low, stable high or reference (no change or increase) and used as the outcome in multinomial logistic regression models. Results: Most LTC categories were associated with adverse patterns of change in grip strength (stable low and/or decline): for example, musculoskeletal/trauma conditions were associated with an increased risk of the stable low pattern (Relative Risk Ratio [RRR] = 1.63; 95% Confidence Interval [CI] 1.49–1.79). Multimorbidity and lifestyle factors had independent associations with grip strength change: those with 3+ categories of LTCs were more likely to experience decline in grip strength (RRR = 1.18;95% CI 1.08–1.28) compared to those with no LTCs. Low physical activity was associated with adverse patterns of grip strength, while raised BMI had divergent associations (both the decline and stable high patterns of grip strength change). Conclusion: Individuals living with multimorbidity and those with lifestyle risk factors such as low physical activity are at increased risk of loss of strength over time.